Membangun kinerja yang optimal melalui analisis jabatan dan struktur organisasi dalam profesionalisme kerja pegawai bagian organisasi Sekretariat Daerah Kota Malang - Hafidzah, Nur (Maliki Interdisciplinary Journal, 2023)
Job analysis in an organization provides a deep understanding of the duties or responsibilities that must be carried out in a particular position. With job analysis, the organization will be helped in preparing the organizational structure. Job analysis is a method that can be used in human resource management to identify the duties, responsibilities, and requirements associated with a position that can be seen through job analysis. This paper aims at how important job analysis and organizational structure are to create work professionalism by achieving employee performance. So that it will create an advanced organization and the achievement of optimal public services. The data for this research comes from observation, interviews with employees, documents regarding job analysis, and literature. The results of this study explain that job analysis has the most important element in the organization, with the implementation of job analysis will provide a more detailed explanation to employees regarding the tasks that must be carried out properly. Thus, employees will have professionalism and achieve an optimal level of employee performance quality.